Faith in the Digital Age: Analyzing Religious Imagology through the Virtual Sorogan Tradition - Effendi, Dudy Imanuddin; Sarbini, Ahmad; Lukman, Dede (UIN Sunan Gunung Djati Bandung, 2025)
This study examines a digital da'wah model promoting religious moderation through the yellow book chanting tradition broadcasted via live streaming on YouTube channels, including Al-Bahjah TV, Ngaji Gus Baha Official, and Ulil Abshar Abdalla. Employing a qualitative approach within a critical paradigm, the research analyzes the historical, social, cultural, economic, and political contexts of digital da'wah. The sorogan tradition is explored using descriptive-qualitative methods and virtual ethnography to capture online interactions. Data were collected through participant observation, interviews, focus group discussions, and documentary analysis. Findings reveal that these channels effectively strengthen religious knowledge among the younger generation through engaging content and innovative visual communication. The sorogan tradition fosters virtual social relationships at individual and group levels, contributing to a relevant da'wah ecosystem in the digital era.